User-Generated Translation Community in Online Video Streaming: The Social-Digital Dynamics of YouTube-Focused Fansubbing Channels on Bilibili - Sijing Lu (SAGE Open)
This article is inspired by the considerable popularity of subtitled translations of YouTube videos in Mandarin on Bilibili, one of the largest online video streaming sites in China. Drawing on Bourdieu’s field theory reframed for digital media, this article uses Youzimu, a YouTube-focused fan subtitling channel on Bilibili, as a case study to explore how Youzimu fosters a self-mediating network for translating YouTube videos into Mandarin, and the extent to which fan translators reproduce the original YouTube videos through their autonomous endeavors. The results indicate that Youzimu’s self-mediated network is predicated upon the ongoing exchange of diverse forms of capital, affording fan translators within the platform a degree of productive autonomy in their translation efforts. Nevertheless, the channel’s adherence to regulatory frameworks governing online streaming and the unofficially sanctioned status of YouTube within China imply a heteronomous principle of hierarchy within the fan subtitling ecosystem.